2019
DOI: 10.1097/md.0000000000015416
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplements for relieving stress in healthy participants

Abstract: Background: Psychological stress is a ubiquitous subjectively negative emotional experience, but excessive psychological stress has adverse effects on the happiness in our lives and physical and mental health, and may cause many health problems. Studies have found that probiotics have a certain role in alleviating negative emotions, reducing abnormal behaviors, improving cognitive function, and also showing the great potential of probiotics in relieving psychological stress. At present, many clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Various prebiotics have enhanced the stress-protective microbial organism’s activity and growth. Therefore, prebiotics in the diet increases the bacterial species to produce lactic acid and butyrate (stress-protective microbial species) and maintain the host from the neurobiological, behavioral, and physiological effects of stress ( 23 , 60 ).…”
Section: Portrayal Of the Effect Of Pro-and Prebiotics On Neurologica...mentioning
confidence: 99%
See 1 more Smart Citation
“…Various prebiotics have enhanced the stress-protective microbial organism’s activity and growth. Therefore, prebiotics in the diet increases the bacterial species to produce lactic acid and butyrate (stress-protective microbial species) and maintain the host from the neurobiological, behavioral, and physiological effects of stress ( 23 , 60 ).…”
Section: Portrayal Of the Effect Of Pro-and Prebiotics On Neurologica...mentioning
confidence: 99%
“…the decline of Bifidobacterium spp. in feces ( 23 ). In addition, it was found that Bifidobacterium longum 1714™ modulated resting neural activity, enhanced mental vitality, and attenuated mental fatigue which leads to neural response modulation during stress ( 61 ).…”
Section: Portrayal Of the Effect Of Pro-and Prebiotics On Neurologica...mentioning
confidence: 99%
“…Moreover, the diversity of the gut microbiome has been shown to regulate cognitive behaviour by promoting the synthesis of essential neurotransmitters and neuropeptides in rodents (Desbonnet et al, 2015) [46] . Additionally, probiotics have been associated with restoring gut homeostasis, thereby reducing anxiety and alleviating stress levels in individuals (Scott et al, 2013; Zhang et al, 2019) [126,114] . Research into farm animals has shown that the gut microbiome has the potential to influence stress levels in dairy animals, mirroring findings in humans.…”
Section: The Gut-brain Connection: Probiotics As Stress Regulatorsmentioning
confidence: 99%
“… 13 These complications can be treated and prevented by the use of probiotics. Moreover, probiotics are also beneficial in the management of health conditions other than GIT like urinary tract 14 and respiratory tract infections, 15 allergies, 16 obesity, 17 stress 18 and cardiovascular disorders. 19 …”
Section: Introductionmentioning
confidence: 99%